Synthesis and Characterization of Mesoporous Carbon Supported Ni-Ga Catalyst for Low-Pressure CO2 Hydrogenation - Uwin Sofyani; Yuni Krisyuningsih Krisnandi; Iman Abdullah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this study, the atmospheric-pressure hydrogenation of CO2 was carried over bimetallic Ni-Ga catalyst supported on mesoporous carbon (MC). MC was successfully prepared using the soft-template method as proven by Fourier Transform Infra Red (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy - Energy Dispersive X-Ray Spectroscopy (SEM-EDS), Brunauer–Emmett–Teller Surface Area Analyzer (BET SAA), and Transmission Electron Microscopy (TEM) characterizations. The Ni-Ga/MC catalyst was synthesized using the impregnation method, and based on the XRD characterization, the formation of bimetallic Ni-Ga on the MC support is confirmed. The EDS mapping image shows the uniform distribution of the bimetallic Ni-Ga on the MC surface, especially for the Ni5Ga3/MC and NiGa3/MC catalysts. Moreover, the TEM images show an excellent pore size distribution. The formation of Ni-Ga alloy was identified as an active site in the CO2 hydrogenation. Ni5Ga3/MC catalyst exhibited a 10.80% conversion of CO2 with 588 μmol/g formaldehyde at 1 atm, 200 °C, and H2/CO2 ratio of 3/1. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).